Higher education policy: A case study on quality assessment towards a model of university management. (Avaliação: Revista da Avaliação da Educação Superior, 2016)
The institutional self-assessment is considered herein in the context of higher education assessment as a university management tool. The paper aims to present and discuss the impact of the results of an institutional self-assessment committee in the management of pedagogical and administrative issues of a Brazilian university in accordance with contemporary education policy. Four consecutive annual reports were reviewed to demonstrate the impacts of institutional self-evaluation and to raise questions about the academic community. Content analysis principles were used to validate the assumptions of the committee’s annual routines regarding the importance of the institutional assessment framework as the basis for the qualification of academic procedures. It was possible to observe the positive effects of the committee on the university’s practices: the effective participation of the academic community in the evaluation processes as well as validation of the information for university management. Another aspect that the evaluation allowed was the identification of areas of greater or lesser impacts on the scientific, social, pedagogical and technological aspects. The role of the committee was essential in identifying strengths and weaknesses, thus contributing towards performing actions to improve the institutional quality of the University of Uberaba under the panorama of Brazilian higher education assessment.